3D porous nanostructured Ni3N–Co3N as a robust electrode material for glucose fuel cell. Issue 11 (11th February 2020) - Irfan, Muhammad; Khan, Izhar Ullah; Wang, Jiao; Li, Yang; Liu, Xianhua
Abstract : Metal nitrides are broadly applicable in the field of electrochemistry due to their excellent electrical properties. 3D nanostructured Ni3 N–Co3 N catalyst was prepared and tested as anode catalyst for a glucose fuel cell. Abstract : Metal nitrides are broadly applicable in the field of electrochemistry due to their excellent electrical properties. In this study, a 3D nanostructured Ni3 N–Co3 N catalyst was prepared by using a versatile urea glass method, and was tested as an anode catalyst for a glucose fuel cell. The synthesized Ni3 N–Co3 N exhibits uniform particle dispersion in structure, morphology, and composition, and has a interpenetrating three-dimensional network structure. Notably, the Ni3 N–Co3 N significantly improved the catalytic activity of glucose oxidation compared to Ni3 N, Co3 N, and conventional activated carbon electrodes. The superior electrochemical performance could be attributed to its porous structure and unique properties, which provided a fast transport network for charge and mass transfer as well as good synergetic effect. The glucose fuel cell equipped with a Ni3 N–Co3 N anode achieved 30.89 W m −2 power and 97.66 A m −2 current densities at room temperature. This investigation provides potential directions for the design of cost-effective bimetallic catalysts for a wide range of glucose fuel cell applications.